THE EFFECT OF PERSONAL PHOTOGRAPH ON STUDENTS’ WRITING QUANTITY IN DESCRIPTIVE TEXT (A Quasi-Experimental Study on the Second Year Students of SMAN 8 Bengkulu in 2006/2007 Academic Year) - Gustian Pelani Gustian Pelani (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2015)
This study was aimed to investigate the effect of personal photographs on students writingquantity of descriptive text. The population of this study was all the students of the secondyear of SMAN 8 Bengkulu in academic year 2006/2007 with the total number of 200 students.The sample of this research was taken by random sampling. By using the cluster-samplingtechnique, 80 students were taken as the samples. The samples divided into two groups,experimental and control group. The instrument employed in this study was writing tests. Thepre-test was conducted before giving treatments in order to know the degree of relevance ofboth groups. In the pre-test analysis, it was found that the t-count < t-table (0,12 < 2,000) forthe analysis amount of words and t-count < t-table (0,26 < 2,000) for the analysis amount ofsentences. It means that there were no significant difference between the two groups scores.Therefore, the two groups can be accepted as the samples of this study. After giving sometreatments to the experimental group, the post-test was held to the both groups. Based on thedata analysis of the post-test, it was found that t-count > t-table (3,76 > 2,000) for theanalysis amount of words and t-count > t-table (4,1 > 2,000) for the analysis amount ofsentences. This finding indicated that there was a significant difference between theexperimental and control group scores. It means that students’ personal photographs had asignificant effect on their writing quantity. In the other words, the use of personal photographscould increase students’ writing quantity especially in descriptive text. Therefore, thistechnique can be applied by teacher as a teaching aid in descriptive text’s writing